2020
DOI: 10.9734/ejnfs/2020/v12i530225
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Overweight, Obesity and the Dietary Habits of Undergraduate Students of Lagos State University

Abstract: Aims: To determine the prevalence of overweight, obesity and dietary habits of under graduate students of Lagos State University. Study Design: The study was a descriptive cross-sectional survey. Place and Duration of Study: Lagos State University, Lagos, Nigeria, between June 2016 and July 2016. Methodology: 150 undergraduate students were selected through multistage random sampling. Information on socio-demographic characteristics, dietary habit and physical activity was obtained using stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The study shows that many of the students had inadequate feeding habits. More than one third of them consumed less than three meals in a day, although this result was higher than the finding of Ukegbu et al (2017) which was 34% and lower than 60.7% of undergraduate students in Cameroun (Niba et al, 2017) and 83% Lagos State University students in Southwest, Nigeria (Arisa et al, 2020). A large proportion of the students skipped meals and breakfast was the frequently skipped meal with about half of them.…”
Section: Feeding Habitsmentioning
confidence: 64%
See 3 more Smart Citations
“…The study shows that many of the students had inadequate feeding habits. More than one third of them consumed less than three meals in a day, although this result was higher than the finding of Ukegbu et al (2017) which was 34% and lower than 60.7% of undergraduate students in Cameroun (Niba et al, 2017) and 83% Lagos State University students in Southwest, Nigeria (Arisa et al, 2020). A large proportion of the students skipped meals and breakfast was the frequently skipped meal with about half of them.…”
Section: Feeding Habitsmentioning
confidence: 64%
“…Recent findings of studies in Southwest region of Nigeria revealed that different level of physical activity and days of physical activity correlated with general and central obesity among university students (Sedodo et al, 2020;Arisa et al, 2020;Ikujenlola & Adekoya, 2020). Lack of physical activity was found to contribute to obesity in 86% of private university students in the region (Okondu et al, 2020).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this regard, undergraduate students are more vulnerable and have high risks to become overweight or obese. Other aspects to adopt poor dietary routines for college students include social setup and high academic demands by which they become prone to alter the sleep restrictions and sleep-wake cycle and often skipping of breakfast (Arisa et al, 2020;Willie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%